KAMS: A Kids’ Athletics Movement Skill Assessment Instrument-Evidence of Content Validity and Reliability in Indonesian Children Aged 10–11 Years - Ricky Wibowo; Agus Mahendra; Yudy Hendrayana; Sucipto Sucipto; Rene II Mediana Babiera (Journal of Sport Science and Education, 2026)
The World Athletics Kids’ Athletics Level 2 programme targets children aged 8–11 years through running, jumping, and throwing activities. However, no standardised and psychometrically validated instrument exists to assess Kids’ Athletics movement skills among Indonesian children. This study developed and validated the Kids’ Athletics Movement Skill Assessment (KAMS), comprising six sub-tests: 30 m Sprint, Hurdles Sprint, Standing Long Jump, Standing Triple Jump, Turbo Throw, and Medicine Ball Push. Following the COSMIN framework, instrument development included item generation, expert content validation, pilot testing (n = 30), and psychometric evaluation with 60 primary school students (30 boys, 30 girls). Content validity was perfect (S-CVI/Ave = 1.00). Inter-rater reliability was excellent (ICC = 0.910), intra-rater reliability ranged from 0.836–0.970, and test-retest reliability ranged from 0.750–0.871. Internal consistency was acceptable (Cronbach’s α = 0.793). The mean total process score was 24.68 ± 3.33, with 83.3% of students achieving at least the Good category. Although boys showed higher throwing and jumping product scores, total process scores did not differ significantly by gender. KAMS demonstrated excellent psychometric properties and is suitable for evaluating Kids’ Athletics programmes in Indonesian primary school children, with further studies recommended to establish construct and concurrent validity.